Dimensional Analysis of Auger‐Type Fast Pyrolysis Reactors. Issue 1 (29th July 2016) - Funke, Axel; Henrich, Edmund; Dahmen, Nicolaus; Sauer, Jörg
Abstract: Modeling of fast pyrolysis reactors is challenging, even with state of the art computational tools and design, because rules to scale up well‐running fast pyrolysis reactors are missing. Dimensional analysis is a classical tool to evaluate complex processes on a scientific basis and its application to fast pyrolysis is presented herein. Using the example of auger‐type fast pyrolysis reactors, it is shown that scale‐up can be reduced to a set of simple design rules. Full similarity of reaction conditions can never be achieved for fast pyrolysis in general, but it is shown which similarities are affected and to which extent they change. Dimensionless numbers derived from this analysis can even be used to describe the influence of parameters on the reactor performance; however, a significant reduction in complexity is required to achieve a practical relevance list. Strategies are outlined to achieve such a reduction based on partial similarities of rate‐determining steps. Abstract : Easy rules : Modeling of fast pyrolysis reactors is difficult, even with state of the art computational tools, because of the complex interactions that take place and multiple challenges of quantifying them. Dimensionless numbers derived from a dimensional analysis can be used to derive a simple set of design rules for the scale‐up of well‐running reactors; these are demonstrated by using auger‐type reactors as an example.